Pengembangan Agribisnis Ikan Balita di UD Suhada, Kabupaten Cianjur - Andi Asrianto Iskandar; Sapta Raharja; Komar Sumantadinata (Institut Pertanian Bogor, 2013)
The world market demand for fishery products is increasing even frequently not fulfilled. It required an effort to overcome the problems in fulfilling the demand for fishery products. Types of freshwater fish cultivated for balita fish at UD Suhada is a type of tilapia and goldfish. The purpose of this study is to examine the feasibility of balita fish agribusiness investment in UD Suhada; identify the internal and external factors that influence the development of agribusiness balita fish at UD Suhada; formulate and recommend appropriate alternative development strategies to be applied to agribusiness balita fish at UD Suhada in business development. Methods of data collection using purposive sampling method, is by deliberately selecting the sample to be studied as a respondent. Respondents were selected from the management and the workers UD Suhada. Financial analysis at 14 percent of interest rate and 5 years of project lifetime resulted in feasible decision with Rp1,105,005,110 of NPV; 4.85 of net B/C Ratio; 38.95 percent of IRR, 3 years and 5 month of PBP; and Rp1,522,035,876 or 32.725 kg of BEP. The combination of value IFE EFE values for 2.688 and 2.651 in the IE matrix shows that the position of the business in V (five) cells, that cell growth. Based on the SWOT analysis and QSPM analysis the strategic priorities is to create a diverse variety of products while maintaining the quality of balita fish, extending the range of distribution and marketing, in collaboration with researchers in developing the quality of balta fish products to face competition.Key words: balita fish, business feasibility, agribusiness, business development strategy